Analisis Pertumbuhan Ekonomi Di Provinsi Jawa Timur Tahun 2022 - Muhammad Alfin Syaiful Izza; Fitri Luthfia Wachdah; Muhammad Yasin (Trending: Jurnal Manajemen dan Ekonomi, 2023)
The success of a country in improving the welfare of its people can be measured by the level of economic growth that has been achieved, high and stable economic growth from year to year means that people's welfare has increased. East Java Province is the second largest contributor to the Indonesian economy with a growth rate on par with the national level and other major provinces in Java. The purpose of this study is to analyze the level of economic growth in East Java province in 2022. This research uses a qualitative method with a library research approach. The results of this study show that the East Java Economy in 2022 will experience a growth of 5.34 percent. Growth occurred in almost all business fields except Mining and Quarrying. Business fields that experienced significant growth were Transportation and Warehousing.